A complex intervention to reduce antibiotic prescribing in rural China: a cluster randomised controlled trialResearch in context - Xingrong Shen; Beth Stuart; Enci Cui; Rong Liu; Tingting Zhang; Jing Chai; Wenjuan Cong; Xiaowen Hu; Isabel Oliver; Guiqing Yao; Paul Little; Helen Lambert; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Excessive use of antibiotics is a widespread problem. We aim to evaluate the efficacy of a multifaceted intervention for reducing antibiotic use in patients with respiratory tract infections (RTIs). Methods: In this two-arm cluster randomized controlled trial, we enrolled patients aged 18+ with symptomatic RTIs at 40 township health centers (THCs) selected from 10 counties in Anhui, China. The THCs were randomized using an online tool (‘Sealed Envelope’) to intervention or usual care (1:1 ratio), stratified by baseline antibiotic prescribing and with random block sizes (4 or 6). The intervention had five components: a half-day clinician training, a WeChat-based peer support group, a decision aid, a poster commitment letter and a patient leaflet. The primary outcome was whether antibiotics were prescribed at the index consultation. Secondary measures included defined daily dose (DDD), illness recovery rate, re-visits to other care-givers or retail pharmacies and incremental cost-effectiveness ratio (ICER). These measures were analyzed using generalized linear mixed modeling controlling for clustering. The study was registered as ISRCTN30652037. Findings: Between December 2021 and September 2022, 1053 patients were recruited (intervention, 21 THCs, n = 552; control, 19 THCs, n = 501), using consecutive sampling. Antibiotic prescribing rate was 55.25% and 66.67% in the intervention and control arms (Odds ratio 0.52, 95% confidence interval [CI]: 0.27, 0.98; p = 0.044). The intervention group also had lower, significant or non-significant, differences for other markers of antibiotic use: DDD (1.57 vs 2.75); prescriptions of two or more types of antibiotics (9.78% vs 11.58%); obtaining antibiotics from retail pharmacies (3.68% vs 5.78) or from other clinics (2.70% vs 4.05%). The intervention resulted in a cost reduction of 9.265 RMB (1.471 USD) per consultation episode and an ICER of −7769.98 RMB or −1233.33 USD/QALYs. The intervention did not encounter any major adverse event. Interpretation: The intervention package was effective and cost-effective in reducing antibiotics prescribing without adverse effects. Funding: The trial was supported by National Natural Science Foundation of China (No. 81861138049) and United Kingdom Research Innovation (No. MR/S013717/1).